Educação em saúde com o uso de mídias digitais para o bem-estar emocional de idosos: pesquisa-ação - Pires, José Iury Ferreira (2023)
This work aims to evaluate the impact of the use of digital media on the health education process and on the emotional well-being of older adults from a Family Health Strategy and the Reference Center for the Elderly in the city of João Pessoa, Northeast Brazil. Method: this is an action research with a quantitative-qualitative approach while considering both human subjectivity and the use of validated psychometric instruments for the screening of anxiety, using the Beck Anxiety Inventory (BAI), depression with the Patient Health Inventory (PHQ-9) and quality of life with the SF-36. The research was conducted through virtual rooms by WhatsApp, where weekly meetings took place with themes chosen by the elderly, bringing information and health education to the participants. Eighteen elderly women aged 60 to 80 years participated in this research. The selection was non-probabilistic for convenience. The health education process was carried out with aspects of the theme analyzed, occurring in eight meetings. Data were collected through interviews and questionnaires based on two semi-structured scripts, before and after the educational period, in order to perform a comparative analysis of the two moments, where descriptive and inferential statistics were used, as well as Bardin's thematic analysis for qualitative evaluation. Results: Although the elderly do not belong to the generation of digital natives, they have a certain understanding of what Digital Social Networks (DSN) are and their majority are active in social interaction applications such as WhatsApp, presenting 44.4% of exclusive use on this platform because it has greater ease of handling and accessibility. It was observed in the interventions that the lack of knowledge reduces mental health care. After the intervention, a statistically significant improvement in mental health was evidenced, obtaining a reduction in signs and symptoms of anxiety, obtaining differences from the medians of 7.5 in the first application to 4.0 in the second application, being p < 0.001, in the same way there was a decrease in signs and symptoms of depression, obtaining in the first application a median of 3.5 to 1.5 in the second application, being p < 0.001, improving mental health care and healthy practices, resulting in the improvement of 5 of 8 domains investigated by the quality of life instrument, namely: limitation by physical aspects, general health status, vitality, social aspects and mental health, where p < 0.001. The process of health education through the use of digital tools with the aid of social networks in educational interventions has the potential to improve knowledge and stimulate emotional well-being in the elderly population, highlighting the importance of using resources such as this in health education actions.